La gestion des communications par le contexte - Jacques Leplat (Perspectives Interdisciplinaires sur le Travail et la Santé)
The theme of this paper is addressed from the perspective of ergonomics psychology, in that it considers communications as components of activity that must therefore be studied in conjunction with the activity and context within which they take place. Through the relations between context and communications, the paper aims in particular to determine how an action on the context may modify communications. By examining both notions jointly, it should be possible to identify some ergonomic impacts for communications management, which is defined here as the place of communications within the activity, and in particular their function in connection with the general goal of the activity within its context.The paper begins by discussing some terminological problems concerning the notions of context and communications, with emphasis on references to the notion of activity. It then considers three aspects of the interaction between context and communications : - 1) context as a modulator of the meaning of communication ; - 2) context as a means of communication ; - 3) context as a product of communication. Lastly, some negative impacts of context on communications are briefly mentioned. In conclusion, the paper makes some suggestions for ergonomic analysis of activity in work situations, in the form of a grid of questions developed from the research.